SISTEM INFORMASI REKAM MEDIS PASIEN RAWAT JALAN DI UPTD PUSKESMAS KUNINGAN BERBASIS WEB - Tatang Saputra; Erik Kurniadi (FKOM UNIKU, 2019)
Puskesmas is a level 1 health facility. More than 40% of Indonesia's population uses health services at the Puskesmas. It is interesting that the Puskesmas is the health care provider that is closest to the community. Recording medical records of patients at the Kuningan Health Center is still done manually. Data search has time constraints. This happens because the same data is often found. Ineffective management of medical records will become a major problem in health services at the Puskesmas. This problem must be overcome so that the puskesmas has good data and information. One way to overcome this problem is to build a computerized medical record information system. Medical Record is a compilation of facts about the health and illness of a patient. Medical Records become a very important thing in the delivery of health services. Because the importance of a medical record, the author is interested in conducting research with the title